Ethylene-vinyl acetate copolymer resin and molded body and film containing same
By optimizing the vinyl acetate content and molten viscoelastic storage modulus of ethylene-vinyl acetate copolymer resins, the challenges of achieving high heat resistance, transparency, and ESCR are addressed, resulting in improved performance while maintaining processability.
Patent Information
- Application Number
- JP2021103963
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-21
- Filing Date
- 2021-06-23
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2041-06-23
AI Technical Summary
Ethylene-vinyl acetate copolymer resins face challenges in achieving high heat resistance, transparency, and environmental stress cracking resistance (ESCR) while maintaining processability, as increasing vinyl acetate content improves transparency and flexibility but decreases heat resistance, and increasing molecular weight improves ESCR but reduces processability.
The development of an ethylene-vinyl acetate copolymer resin with a vinyl acetate unit content between 3.0% and 30.0% by mass, characterized by a specific molten viscoelastic storage modulus profile during temperature reduction, which satisfies certain mathematical criteria to optimize heat resistance, transparency, and ESCR.
This approach results in an ethylene-vinyl acetate copolymer resin with enhanced heat resistance, transparency, and ESCR, while maintaining suitable processability, thereby addressing the limitations of existing technologies.
Smart Images

Figure 0007661151000003 
Figure 0007661151000004 
Figure 0007661151000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an ethylene-vinyl acetate copolymer resin and a molded article and film containing the same. [Background technology]
[0002] Ethylene-vinyl acetate copolymer resin has excellent performance properties such as transparency, flexibility, mechanical strength, electrical insulation, weather resistance, and durability, and is used in applications such as artificial turf mats, automobile mat guards, and drainage hoses through injection molding or extrusion molding. It is also processed into single-layer or laminated films through inflation or T-die film formation, and is used in a wide range of industrial fields such as agricultural polyolefin films and automobile mudguard covers.
[0003] As a film using an ethylene-vinyl acetate copolymer resin, for example, Patent Document 1 proposes an ethylene-vinyl acetate copolymer film that has high tear strength and heat retention even though it has a high vinyl acetate content.
[0004] Furthermore, for example, Patent Document 2 proposes an ethylene copolymer composition having a vinyl acetate unit content of 20 to 45 wt % and being flexible and having excellent strength, moldability and heat resistance. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2004-161881 A [Patent Document 2] Patent No. 4165963 Summary of the Invention [Problem to be solved by the invention]
[0006] However, while the transparency, flexibility and adhesiveness of ethylene-vinyl acetate copolymer improve with an increase in the vinyl acetate content, the crystallization temperature decreases and the heat resistance tends to decrease.
[0007] In recent years, as the fields in which ethylene-vinyl acetate copolymers are used have expanded, the market has come to demand even more advanced performance. Specific examples of the required performance include high transparency to enhance design, and in applications such as drainage pipes, artificial turf, and automobile mudguard covers, where the materials are in contact with various liquids and exposed to stresses such as internal pressure for long periods of time, the materials must not suffer from environmental stress cracking when left in chemicals under a certain level of stress, i.e., they must have high environmental stress cracking resistance (hereinafter also referred to as "ESCR"). Furthermore, from the perspective of the environmentally conscious Sustainable Development Goals (SDGs), extending product life will enable a reduction in the amount of ethylene-vinyl acetate copolymer used as a raw material in the long term, so there is a demand for ethylene-vinyl acetate copolymers with high ESCR and the ability to extend product life. Generally, methods for increasing the ESCR include increasing the molecular weight of an ethylene-vinyl acetate copolymer resin and increasing the vinyl acetate content, but increasing the molecular weight tends to decrease processability, and increasing the vinyl acetate content tends to decrease heat resistance as described above. Therefore, there is a demand for an ethylene-vinyl acetate copolymer resin that is excellent in heat resistance, transparency, and ESCR.
[0008] The ethylene-vinyl acetate copolymer film described in Patent Document 1 has room for improvement in terms of transparency and ESCR because the vinyl acetate content at each molecular weight of the ethylene-vinyl acetate copolymer decreases as the molecular weight increases. Also, the ethylene copolymer composition described in Patent Document 2 is a composition consisting of polyethylene and ethylene-vinyl acetate copolymer, and since polyethylene and ethylene-vinyl acetate copolymer are not completely compatible with each other, there is room for improvement in terms of poor transparency, etc.
[0009] Therefore, an object of the present invention is to provide an ethylene-vinyl acetate copolymer resin excellent in heat resistance, transparency and ESCR, and a molded article and film containing the same. [Means for solving the problem]
[0010] Means for Solving the Problems The present inventors conducted intensive research to solve the above problems, and as a result, discovered that an ethylene-vinyl acetate copolymer resin having a storage modulus of melt viscoelasticity in a predetermined range during transition from a molten state to a solidified state (measured under specific temperature-dropping conditions) can solve the above problems, thereby completing the present invention.
[0011] That is, the present invention is as follows. [1] The content of vinyl acetate units is 3.0% by mass or more and 30.0% by mass or less, An ethylene-vinyl acetate copolymer resin, in which the storage modulus G' during the temperature-lowering process under the temperature-lowering measurement conditions of the melt viscoelasticity measurement described below satisfies the following formula (1) within a range satisfying the following formula (2). Tb-Te≦10.00 (1) (In formula (1), Tb is the maximum temperature (°C) within the range satisfying the following formula (2), and Te is the minimum temperature (°C) within the range satisfying the following formula (2).) |(dlogG' / dT)|≧0.04 (2) (In formula (2), |(dlogG' / dT)| is the degree of change in storage modulus G' (Pa) with respect to the change in temperature T (°C).) (Melt viscoelasticity measurement conditions) Measurement device: ARES-G2 (manufactured by TA Instruments) Atmosphere: Nitrogen Geometry: 8mmφ parallel plate Gap distance: 1.5mm Distortion: 5.0% at 105°C or more and 200°C or less, 3.0% at 45°C or more and less than 105°C, 0.1% at 30°C or more and less than 45°C. The temperature indicated is the temperature directly below the disk of the parallel plate. Temperature drop measurement conditions: The sample is placed in an apparatus set to 200°C and held for 10 minutes. The sample is then cooled from 200°C to 30°C at a rate of 5°C / min, and the melt viscoelasticity of the sample is measured as it cools. [2] The ethylene-vinyl acetate copolymer resin according to [1], wherein a storage modulus G' during a temperature-lowering process under temperature-lowering measurement conditions in the melt viscoelasticity measurement satisfies the following formula (3): |(dlogG' / dT)| MAX ≧-0.0125×VA content+0.490 (3) (In formula (3), |(dlogG' / dT)| MAX is the maximum value of the degree of change in storage modulus G' (Pa) with respect to the change in temperature T (°C), and the VA content is the content (mass%) of vinyl acetate units in the ethylene-vinyl acetate copolymer resin. [3] The ethylene-vinyl acetate copolymer resin according to [1] or [2], wherein the ethylene-vinyl acetate copolymer resin has a molecular weight distribution (Mw / Mn) of 8.0 or less. [4] The ethylene-vinyl acetate copolymer resin according to any one of [1] to [3], wherein the ethylene-vinyl acetate copolymer resin has an MFR of 0.1 g / 10 min or more and 5.0 g / 10 min or less. [5] A molded article comprising the ethylene-vinyl acetate copolymer according to any one of [1] to [4]. [6] A film comprising the ethylene-vinyl acetate copolymer according to any one of [1] to [4].[7] A laminate film comprising the ethylene-vinyl acetate copolymer according to any one of [1] to [4]. Effect of the Invention
[0012] According to the present invention, it is possible to provide an ethylene-vinyl acetate copolymer resin having excellent heat resistance, transparency and ESCR, and a molded article and a film containing the same. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 shows a schematic diagram of an example of a graph showing a change in storage modulus G′ during a temperature drop process under specific temperature drop measurement conditions in melt viscoelasticity measurement. [Diagram 2]FIG. 2 shows a conceptual diagram of an example of a graph of |(dlogG' / dT)|, which shows the degree of change in storage modulus G' with respect to temperature change in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, the embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. Note that the present invention is not limited to the following description, and can be practiced in various modifications within the scope of the gist of the present invention.
[0015] [Ethylene-vinyl acetate copolymer resin] The ethylene-vinyl acetate copolymer resin of the present embodiment is The vinyl acetate unit content is 3.0% by mass or more and 30.0% by mass or less, and the storage modulus (G') during the temperature drop process under the temperature drop measurement conditions of the melt viscoelasticity measurement described below satisfies the following formula (2) within a range satisfying the following formula (1). Tb-Te≦10.00 (1) (In formula (1), Tb is the maximum temperature (°C) within the range satisfying the following formula (2), and Te is the minimum temperature (°C) within the range satisfying the following formula (2).) |(dlogG' / dT)|≧0.04 (2) (In formula (2), |(dlogG' / dT)| is the degree of change in storage modulus G' (Pa) with respect to the change in temperature T (°C).) (Melt viscoelasticity measurement conditions) Measurement device: ARES-G2 (manufactured by TA Instruments) Atmosphere: Nitrogen Geometry: 8mmφ parallel plate Gap distance: 1.5mm Distortion: 5.0% at 105°C or more and 200°C or less, 3.0% at 45°C or more and less than 105°C, 0.1% at 30°C or more and less than 45°C. The temperature indicated is the temperature directly below the disk of the parallel plate. Temperature drop measurement conditions: The sample is placed in an apparatus set to 200°C and held there for 10 minutes, then the temperature of the sample is lowered from 200°C to 30°C at a rate of 5°C / min, and the melt viscoelasticity of the sample is measured as the temperature is lowered.
[0016] When the ethylene-vinyl acetate copolymer resin of the present embodiment satisfies the above requirements, a molded article or film containing the ethylene-vinyl acetate copolymer resin exhibits high heat resistance, high transparency, and excellent ESCR.
[0017] The ethylene-vinyl acetate copolymer resin of this embodiment will be described below.
[0018] (VA content) The ethylene-vinyl acetate copolymer resin of the present embodiment is a copolymer containing ethylene units and vinyl acetate units.
[0019] The ethylene-vinyl acetate copolymer resin of the present embodiment has a vinyl acetate unit content (hereinafter also referred to as "VA content") of 3.0 mass% or more and 30.0 mass% or less, preferably 4.0 mass% or more and 25.0 mass% or less, more preferably 10.0 mass% or more and 20.0 mass% or less, and even more preferably 13.0 mass% or more and 19.0 mass% or less, based on the total amount of the ethylene-vinyl acetate copolymer resin, from the viewpoints of processability, heat resistance, and flexibility.
[0020] The method for adjusting the VA content to 3.0 mass % or more and 30.0 mass % or less is not particularly limited, but examples thereof include appropriately adjusting the amount of vinyl acetate monomer added in the step of polymerizing the ethylene-vinyl acetate copolymer resin, the polymerization temperature, and the polymerization pressure.
[0021] The VA content can be measured in accordance with JIS K7192:1999 by preparing a calibration curve by saponification and potentiometric titration as a standard test method, and converting it into vinyl acetate by infrared spectroscopy as a control test method. Specifically, the VA content can be measured by the method described in the examples below.
[0022] In the ethylene-vinyl acetate copolymer resin of the present embodiment, the content of ethylene units is, from the viewpoints of processability, heat resistance, and flexibility, preferably 70.0 mass% or more and 97.0 mass% or less, more preferably 75.0 mass% or more and 96.0 mass% or less, even more preferably 80.0 mass% or more and 90.0 mass% or less, and even more preferably 81.0 mass% or more and 87.0 mass% or less, based on the total amount of the ethylene-vinyl acetate copolymer resin.
[0023] The ethylene-vinyl acetate copolymer resin of the present embodiment may contain monomer units other than ethylene units and vinyl acetate units. The other monomer units are not particularly limited, but may be, for example, units derived from propylene, butane, etc. The content of the other monomer units is preferably 30% by mass or less, more preferably 15% by mass or less, and even more preferably 5% by mass or less.
[0024] The ethylene-vinyl acetate copolymer resin of the present embodiment may be a dry blend or melt blend of two or more ethylene-vinyl acetate copolymer resins in any ratio. When two or more ethylene-vinyl acetate copolymer resins are used, it is preferable that the VA content and the like of the entire resins are within the above-mentioned range.
[0025] (Tb, Te, |(dlogG' / dT)|) The ethylene-vinyl acetate copolymer resin of this embodiment satisfies the following formula (1) within a range in which the storage modulus G' during the temperature drop process under the temperature drop measurement conditions of the above-mentioned melt viscoelasticity measurement satisfies the following formula (2). Tb-Te≦10.00 (1) (In formula (1), Tb is the maximum temperature (°C) within the range satisfying the following formula (2), and Te is the minimum temperature (°C) within the range satisfying the following formula (2).) |(dlogG' / dT)|≧0.04 (2) (In formula (2), |(dlogG' / dT)| is the degree of change in storage modulus G' (Pa) with respect to the change in temperature T (°C).)
[0026] When the storage modulus G' of the ethylene-vinyl acetate copolymer resin of this embodiment is measured against temperature change under specific temperature drop measurement conditions for observing the change from a molten state to a solidified state in the above-mentioned melt viscoelasticity measurement, for example, a curve as shown in FIG. 1 (hereinafter referred to as the storage modulus (G') curve) is obtained.
[0027] Furthermore, if the storage modulus (G') curve is converted into "|(dlogG' / dT)|", which represents the degree of change in storage modulus G' (Pa) with respect to change in temperature T (°C), a curve such as that shown in Figure 2 is obtained.
[0028] The peak of |(dlogG' / dT)| corresponds to the state change process from the molten state to the solidified state in the melt viscoelasticity measurement (temperature decreasing measurement condition). This rising process of |(dlogG' / dT)| is due to the position of the molecules of the ethylene-vinyl acetate copolymer resin being fixed and their free movement being stopped, and the closer the slope of the storage modulus (G') curve under temperature decreasing conditions is to 0, the slower the speed at which the free movement of the molecules is stopped, i.e., the slower the crystallization speed.
[0029] In this embodiment, among the values of "|(dlogG' / dT)|" which show the degree of change in storage modulus G' (Pa) with respect to the change in temperature T (°C), when the material changes from a molten state to a solidified state and the temperature is further lowered, crystallization proceeds slightly. Therefore, the crystallization rate is expressed by Tb-Te, where Tb is the maximum temperature and Te is the minimum temperature, which are obtained from the range satisfying the above formula (2) taking into account the measurement error.
[0030] The storage modulus is generally measured by measuring the change from a solid state to a molten state, but in this embodiment, the change from a molten state to a solidified state is measured, which is characteristic. The crystallization rate can be obtained by measuring the storage modulus accurately by high-speed sampling at 1 point / second for the rapid change in storage modulus when the state changes from the molten state to the solidified state. As a method for obtaining the crystallization rate from the state change from the molten state to the solidified state, a method is known in which the crystallization temperature is measured by differential scanning calorimetry (hereinafter referred to as DSC measurement), the 1 / 2 isothermal crystallization time is obtained when the temperature is raised from the ONSET temperature of the crystallization temperature by +1°C to +4°C, the measured temperature (1 / T) and the 1 / 2 isothermal crystallization time are plotted to obtain an approximate straight line, and the crystallization rate is obtained from the slope, but this does not match the result of the crystallization rate represented by Tb-Te in this embodiment. It is speculated that the above difference occurs because the crystallization rate determined by DSC measurement measures static crystallization behavior with little strain during the process of changing from a molten state to a solidified state, whereas the storage modulus measurement under cooling conditions measures the crystallization rate under a constant strain and shows dynamic crystallization behavior. Therefore, it is speculated that the storage modulus measurement under cooling conditions shows the crystallization rate during processing of the actual product.
[0031] In this embodiment, Tb-Te is 10.00 or less, preferably 9.50 or less, more preferably 9.00 or less, and further preferably 8.50 or less. The lower limit of Tb-Te is not particularly limited, but is, for example, 5.00 or more.
[0032] When Tb-Te is 10.00 or less, the crystallization rate of the ethylene-vinyl acetate copolymer resin is fast, so that the crystal sizes are uniform and small, and there are many tie molecules connecting the crystals. As a result, the ethylene-vinyl acetate copolymer resin of this embodiment exhibits excellent transparency, and a molded product with excellent ESCR can be obtained.
[0033] The method for controlling Tb-Te to the above-mentioned predetermined value is not particularly limited, but examples thereof include a method for removing impurities in the vinyl acetate constituting the ethylene-vinyl acetate copolymer resin, and / or a method for suppressing the generation of low molecular weight components due to decomposition of the obtained ethylene-vinyl acetate copolymer resin. The method for removing impurities in the vinyl acetate constituting the ethylene-vinyl acetate copolymer resin is not limited to the following, but examples thereof include (i) a method for recovering unreacted vinyl acetate monomer and removing impurities by-produced in the reaction in a purification process, and (ii) a method for removing polymerization inhibitors and the like contained in newly used vinyl acetate, in the production process of the ethylene-vinyl acetate copolymer resin, and the like. By carrying out both of the above-mentioned methods (i) and (ii), Tb-Te tends to be able to be controlled to the above-mentioned predetermined value. In addition, the method of suppressing the generation of low molecular weight components due to decomposition of the obtained ethylene-vinyl acetate copolymer resin includes, but is not limited to, a method of controlling the inlet temperature of the ethylene-vinyl acetate copolymer resin and unreacted components when introduced into a high-pressure separator within a specific range when polymerizing by a tubular method. Specifically, for example, when the pressure of ethylene-vinyl acetate copolymer resin polymerized under high temperature and high pressure is reduced, the temperature tends to rise due to the inverse Joule-Thomson effect, so a method of suppressing the temperature rise of the ethylene-vinyl acetate copolymer resin passing through the piping by lowering the average polymerization temperature or the outer jacket temperature by using a double pipe after polymerization can be mentioned. The time for passing through the piping leading to the high-pressure separator while reducing the pressure of the ethylene-vinyl acetate copolymer resin polymerized under high temperature and high pressure is only a short time of a few seconds, but by controlling the temperature during passage, it tends to be possible to suppress the generation of low molecular weight components due to the decomposition of the ethylene-vinyl acetate copolymer resin.
[0034] (|(dlogG' / dT)| MAX ) The ethylene-vinyl acetate copolymer resin of the present embodiment preferably has a storage modulus (G') during the temperature drop process under the temperature drop measurement conditions of the melt viscoelasticity measurement described above that satisfies the following formula (3). |(dlogG' / dT)| MAX ≧-0.0125×VA content+0.490 (3) (In formula (3), |(dlogG' / dT)| MAX is the maximum value of the degree of change in storage modulus G' (Pa) with respect to the change in temperature T (°C), and the VA content is the content (mass%) of vinyl acetate units in the ethylene-vinyl acetate copolymer resin.
[0035] In this embodiment, |(dlogG' / dT)| MAX indicates the maximum value of |(dlogG' / dT)| in the graph shown in FIG.
[0036] The total amount of change in (dlogG' / dT) (i.e., the area between Td and Te of the change in G' in the graph shown in Figure 2) correlates with the crystallinity and tends to correlate with the VA content of the ethylene-vinyl acetate copolymer resin. Therefore, the total amount of change in |(dlogG' / dT)| with respect to the VA content tends to be larger as the VA content increases and tends to be smaller as the VA content decreases.
[0037] In this embodiment, the maximum absolute value of (dlogG' / dT) is |(dlogG' / dT)| MAX represents the inflection point of the crystallization rate, and |(dlogG' / dT)| MAX The larger the value of |(dlogG' / dT)|, the faster the crystallization rate. Even if the total change in G' is the same, |(dlogG' / dT)| MAX The larger the gradient of the change in G' with respect to temperature change, the greater the |(dlogG' / dT)| MAX becomes larger.
[0038] The ethylene-vinyl acetate copolymer resin of the present embodiment has a storage modulus G' during the temperature drop process under the temperature drop measurement conditions of the melt viscoelasticity measurement described above, where G' is |(dlogG' / dT)| MA X and the VA content, preferably, |(dlogG' / dT)| MAX≧-0.0125×VA content+0.490, and more preferably |(dlogG' / dT)| MAX ≧−0.0125×VA content+0.495, and more preferably |(dlogG′ / dT)| MAX The relationship is ≧-0.0125×VA content+0.500. |(dlogG' / dT)| MAX By satisfying the relationship ≧-0.0125 × VA content + 0.490, the crystallization rate during processing of the ethylene-vinyl acetate copolymer resin is fast, resulting in uniform, small crystal sizes and an increase in the number of tie molecules connecting the crystals, which tends to result in better transparency and ESCR.
[0039] Regarding the storage modulus G' during the temperature drop process under the above-mentioned temperature drop measurement conditions for the melt viscoelasticity measurement, t, |(dlogG' / dT)| MAX The method of controlling the relationship between the VA content and the VA content within the above range is not particularly limited, but may be, for example, a method of removing impurities in the vinyl acetate constituting the ethylene-vinyl acetate copolymer resin. The method of removing impurities in the vinyl acetate constituting the ethylene-vinyl acetate copolymer resin is not limited to the following, but may be, for example, a method of recovering unreacted vinyl acetate monomer in the production process of the ethylene-vinyl acetate copolymer resin and removing impurities by-produced in the reaction in a purification process, and a method of removing polymerization inhibitors and the like contained in newly used vinyl acetate. In particular, a method of purifying the recovered unreacted vinyl acetate monomer to a certain amount or more is effective.
[0040] (Molecular weight distribution (Mw / Mn)) The ethylene-vinyl acetate copolymer resin of this embodiment has a molecular weight distribution (Mw / Mn) expressed as the ratio of the weight average molecular weight to the number average molecular weight determined by gel permeation chromatography (hereinafter also referred to as "GPC"), which is preferably 8.0 or less, more preferably 7.0 or less, and even more preferably 6.0 or less, from the viewpoint of the transparency of the molded article and film to be formed. The lower limit of the molecular weight distribution (Mw / Mn) is not particularly limited, but is, for example, 2.0 or more.
[0041] The method for controlling the molecular weight distribution (Mw / Mn) of the ethylene-vinyl acetate copolymer resin within the above range is not particularly limited, but examples thereof include a method of making the polymerization temperature distribution in a polymerization vessel closer to uniform when polymerizing the ethylene-vinyl acetate copolymer resin, and a method of not using air as a polymerization initiator.
[0042] (MFR) The ethylene-vinyl acetate copolymer resin of the present embodiment has a melt flow rate (MFR) value measured in accordance with JIS K7210:1999 Code D (temperature = 190°C, load = 2.16 kg) of preferably 0.1 g / 10 min or more and 5.0 g / 10 min or less, more preferably 0.2 g / 10 min or more and 4.0 g / 10 min or less, and even more preferably 0.3 g / 10 min or more and 3.0 g / 10 min or less, from the viewpoint of the ESCR of the molded article and film to be formed.
[0043] The method for controlling the MFR of the ethylene-vinyl acetate copolymer resin within the above range is not particularly limited, but for example, a method of adjusting the reaction temperature and / or reaction pressure when polymerizing the ethylene-vinyl acetate copolymer resin can be mentioned. More specifically, when polymerizing the ethylene-vinyl acetate copolymer resin, if the reaction temperature is increased, the MFR of the ethylene-vinyl acetate copolymer resin tends to increase, and if the reaction pressure is increased, the MFR of the ethylene-vinyl acetate copolymer resin tends to decrease.
[0044] [Method of producing ethylene-vinyl acetate copolymer resin] The ethylene-vinyl acetate copolymer resin of the present embodiment is obtained, for example, by polymerization under ultra-high pressure of 100 to 350 MPa using a multi-stage compressor in the presence of a polymerization initiator, although the polymerization method of the ethylene-vinyl acetate copolymer resin of the present embodiment is not limited thereto, but examples thereof include an autoclave method and a tubular method, and the polymerization is preferably performed by the tubular method.
[0045] When polymerization is performed by the tubular method, it is preferable to produce an ethylene-vinyl acetate copolymer resin by polymerization at an average polymerization reaction temperature of 150° C. to 280° C. and a polymerization pressure of 120 MPa to 270 MPa. More preferably, the average polymerization reaction temperature is 180° C. to 240° C. and the polymerization pressure is 180 MPa to 260 MPa. In addition, in order to narrow the molecular weight distribution of the ethylene-vinyl acetate copolymer resin, it is preferable to make the polymerization temperature distribution in the polymerization vessel as uniform as possible.
[0046] In the tubular system, there are two or more points to feed ethylene, vinyl acetate, and a polymerization initiator into the reactor, and the temperature drops once in the vicinity of each feed point due to the introduction of raw materials, but then rises due to the heat of polymerization. In the next feed point, the temperature similarly drops due to the introduction of raw materials, but then rises again due to the heat of polymerization. In this way, the temperature in the reactor can be non-uniform depending on the raw material introduction point, but in this embodiment, it is preferable to set the difference between each high-temperature peak after feeding to 15°C or less, and the difference between the peak temperature and the bottom temperature to 60°C or less.
[0047] The polymerization initiator used in the polymerization of the ethylene-vinyl acetate copolymer resin of this embodiment is not particularly limited, but examples thereof include air, free radical generators such as peroxides, etc. The free radical generators such as peroxides are not particularly limited, but examples thereof include t-butyl-peroxy-2-ethylhexanoate, t-butyl peroxy acetate, t-butyl peroxy pivalate, di-t-butyl peroxide, etc. In order to narrow the molecular weight distribution, it is preferable not to use air as a polymerization initiator.
[0048] When polymerizing the ethylene-vinyl acetate copolymer resin of the present embodiment, a chain transfer agent such as alcohols, alkanes, alkenes, ketones, or aldehydes may be used as necessary to reduce the molecular weight.
[0049] The alcohols are not particularly limited, but examples thereof include methanol, ethanol, normal propyl alcohol, isopropyl alcohol, normal butyl alcohol, and isobutyl alcohol.
[0050] The alkanes or alkenes are not particularly limited, but examples thereof include ethane, propane, propylene, butane, 1-butene, and 2-butene.
[0051] The ketones or aldehydes are not particularly limited, but examples thereof include acetone, methyl ethyl ketone, 2-pentanone, 3-pentanone, 2-hexanone, 3-hexanone, diisobutyl ketone, methyl isopropyl ketone, formaldehyde, acetaldehyde, normal butyraldehyde, isobutyraldehyde, normal valeraldehyde, and isovaleraldehyde.
[0052] The polymerized ethylene-vinyl acetate copolymer resin is preferably separated from the raw material ethylene gas and granulated into pellets by an extruder.
[0053] For example, in the case of using the tubular system, it is preferable to separate the raw material ethylene gas from the ethylene-vinyl acetate copolymer resin while reducing the pressure in a high-pressure separator and a low-pressure separator, and granulate the molten ethylene-vinyl acetate copolymer resin into pellets in an extruder. The inlet temperature of the ethylene-vinyl acetate copolymer resin and unreacted components when introduced into the high-pressure separator is preferably 180° C. or higher and 250° C. or lower, more preferably 190° C. or higher and 240° C. or lower, and even more preferably 200° C. or higher and 235° C. or lower. By introducing the ethylene-vinyl acetate copolymer resin and unreacted components into the high-pressure separator at a temperature in the above range, the ethylene-vinyl acetate copolymer resin and the unreacted components are easily separated, and the generation of low molecular weight components due to decomposition of the ethylene-vinyl acetate copolymer resin tends to be suppressed, and as a result, Tb-Te tends to be controlled to the above-mentioned predetermined value.
[0054] In the high-pressure separator and the low-pressure separator, the molten ethylene-vinyl acetate copolymer resin and unreacted gases such as raw material ethylene gas and vinyl acetate gas exist as a gas-liquid mixed fluid. It is preferable that the unreacted gas is recovered from the upper part of the container of each separator, and 60% to 90%, preferably 70% to 80%, is sent to the inlet of the multi-stage compressor to be reused in the polymerization.
[0055] It is preferable that 10% to 40% and preferably 20% to 30% of the unreacted gas recovered from the upper part of the container of each separator is subjected to a distillation operation in a purification column. The distillation operation is, for example, first, purification column-1 (inner volume: 0.824 m 3 It is preferable to carry out the reaction using a purifying column-1 (temperature: 50°C), sending unreacted gas from the middle stage of the column-1, and flowing a solvent (e.g., isoparaffin) in a shower-like manner from the upper stage, allowing vinyl acetate to be absorbed into the solvent and then dropping it to the bottom of the column for recovery, and recovering ethylene gas from the top of the column. It is preferable to pack the column with a packing material in order to increase the contact between the gas and the liquid. It is preferable to set the pressure in the column to 0.3 MPa or more, and more preferably 0.4 MPa or more, in order to increase the solubility of the gas in the liquid.
[0056] Furthermore, the liquid component containing vinyl acetate recovered in purification tower-1 was purified by purification tower-2 (inner volume: 0.16 m 3) is preferably used for the distillation operation. For example, it is preferable that the purification tower-2 is heated in a reboiler using steam to create a stepwise temperature gradient, with the tower bottom temperature being 130°C and the tower top temperature being 74°C. Also, for example, a liquid component containing vinyl acetate is sent from the middle of the purification tower-2, and vinyl acetate (boiling point: 71°C) is recovered from the tower top due to the difference in boiling points. Since the vinyl acetate recovered from the tower top is recovered in a gaseous state, it is preferable to recover vinyl acetate as a liquid after condensing it using, for example, a condenser using water. Also, for example, it is preferable to separate high-boiling point components such as solvents (e.g., isoparaffin), polymerization initiators, free acid acetic acid (boiling point: 118°C), and other impurities from the tower bottom.
[0057] In this embodiment, it is preferable to perform a distillation operation on the newly received vinyl acetate raw material using the purification column-2. Since about 10 ppm of hydroquinone is added to the newly received vinyl acetate raw material as a polymerization inhibitor for the purpose of preventing polymerization of vinyl acetate molecules during storage, it is preferable to perform a distillation operation in the purification column-2, recover vinyl acetate from the top of the column, and recover and discard impurities such as hydroquinone (boiling point: 287°C) from the bottom of the column.
[0058] It is preferable to recover the unreacted gas, mix the purified vinyl acetate with a freshly received vinyl acetate raw material and the purified vinyl acetate raw material in a certain ratio, and then supply the vinyl acetate to the tube reactor.
[0059] After pelletizing the ethylene-vinyl acetate copolymer resin with an extruder, it is preferable to blow dry air at 30° C. or more and less than 50° C. for 5 hours or more in a silo for storing the pellets. From the viewpoint of removing low molecular weight components, the temperature of the dry air is preferably 30° C. or more and less than 50° C., more preferably 33° C. or more and 47° C. or less, and even more preferably 35° C. or more and 45° C. or less.
[0060] (Additives) The ethylene-vinyl acetate copolymer resin of the present embodiment may contain known additives, such as, for example, antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, antifogging agents, and coloring pigments, as necessary.
[0061] The antioxidant is preferably a phenol-based antioxidant, which is a primary antioxidant, and is not particularly limited, but examples thereof include 2,6-di-t-butyl-4-methylphenol, pentaerythrityl-tetrakis-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, etc. Secondary antioxidants can also be used in combination, and examples thereof include phosphorus-based antioxidants such as tris(2,4-di-t-butylphenyl)phosphite and tetrakis(2,4-di-t-butylphenyl)-4,4-biphenylene-diphosphonite. Examples of phosphorus / phenol-based antioxidants include 6-tert-butyl-4-[3-(2,4,8,10-tetra-t-butyldibenzo[d,f][1,3,2]dioxaphosphepin-6-yloxy)propyl]-o-cresol, and examples of sulfur-based antioxidants include dilauryl-thio-dipropionate.
[0062] [Molded body] The molded article of the present embodiment contains the above-mentioned ethylene-vinyl acetate copolymer resin. The molded article of the present embodiment can be obtained by injection molding or extrusion molding, and can be suitably used for various applications. Specific examples include, but are not limited to, artificial turf mats, automobile mat guards, mudguard covers, drain hoses, etc.
[0063] [Packaging film] The film of the present embodiment contains the above-mentioned ethylene-vinyl acetate copolymer resin. The film of the present embodiment can be suitably used as a packaging film. Specific examples of the film include, but are not limited to, food packaging films, food wrap films, overwrap films, shrinkable overwrap films, and sealant films.
[0064] [Laminated film] The laminated film of this embodiment contains the above-mentioned ethylene-vinyl acetate copolymer resin. The laminated film of this embodiment may have one or more layers made of the above-mentioned ethylene-vinyl acetate copolymer resin, or may have the above-mentioned ethylene-vinyl acetate copolymer resin in all layers. The method for producing the laminated film of this embodiment is not particularly limited, but examples include a method of producing the film by laminating the layers together through a lamination process, or a method of producing the film by a lamination extrusion process. Furthermore, the laminated film may be made of layers of the same material or layers of different materials. EXAMPLES
[0065] The present invention will be specifically described below using examples. Note that the present invention is not limited to these examples. The physical property measuring methods and evaluation methods in the examples and comparative examples are as follows.
[0066] (1) Melt flow rate (MFR) measurement The MFR of the ethylene-vinyl acetate copolymer resin was measured in accordance with JIS K7210:1999 Code D (temperature = 190°C, load = 2.16 kg).
[0067] (2) VA content measurement In accordance with JIS K7192:1999, as the standard test method, a calibration curve was prepared using a VAC standard sample of an ethylene-vinyl acetate copolymer with a known content of vinyl acetate units by saponification and potentiometric titration, and as the control test method, the content of vinyl acetate units (VA content) in the ethylene-vinyl acetate copolymer resin was measured by infrared spectroscopy.
[0068] (3) Melt viscoelasticity measurement Using a TA Instruments ARES-G2, melt viscoelasticity measurements of ethylene-vinyl acetate copolymer resin were carried out in a nitrogen atmosphere using parallel plates with a gap distance of 1.5 mm and a diameter of 8 mmφ, as follows.
[0069] (Temperature drop measurement conditions) A 0.2g sample of ethylene-vinyl acetate copolymer resin was placed in the device, which was set and held at 200°C, and heated for 10 minutes to completely melt it. After melting, the gap distance was adjusted to 1.5 mm, and the sample that protruded from the parallel plate was removed with a spatula. Then, the sample was cooled from 200°C to 30°C at a rate of 5°C / min, while dynamic viscoelasticity measurements were performed in the linear region. The strain was changed depending on the state, and measurements were performed at 200°C or less and 105°C or more: strain amount of 5.0%, less than 105°C and 45°C or more: strain amount of 3.0%, and less than 45°C and 30°C or more: strain amount of 0.1%. The temperature here refers to the temperature directly under the disk of the parallel plate. In the temperature range of less than 105°C and 45°C or more, where the elastic modulus rises sharply due to solidification, data was acquired at a rate of 1 point / second.
[0070] The maximum temperature Tb and the minimum temperature Te were obtained within a range in which the storage modulus (G') during the temperature drop process under the above-mentioned temperature drop measurement conditions for the melt viscoelasticity measurement satisfied the following formula (2), and Tb-Te was calculated. Furthermore, the maximum degree of change in the storage modulus G' (Pa) relative to the change in temperature T (°C) (|(dlogG' / dT)| MAX ) was sought. |(dlogG' / dT)|≧0.04 (2) (In formula (2), |(dlogG' / dT)| is the degree of change in storage modulus G' (Pa) with respect to the change in temperature T (°C).)
[0071] (4) Measurement of molecular weight and molecular weight distribution The weight average molecular weight (Mw) and number average molecular weight (Mn) of the ethylene-vinyl acetate copolymer resin were determined by gel permeation chromatography (GPC). The ratio (Mw / Mn) of the weight average molecular weight (Mw) and number average molecular weight (Mn) determined by GPC was taken as the molecular weight distribution. The GPC measurement was carried out under the following conditions. The molecular weight was calibrated at 12 points in the range of 10,500,000 to 2,060,000 MW (molecular weight) of standard polystyrene manufactured by Tosoh Corporation, and the MW of each standard polystyrene was multiplied by a coefficient of 0.43 to obtain a polyethylene-equivalent molecular weight. A primary calibration line was created from a plot of the elution time and the polyethylene-equivalent molecular weight, and the weight average molecular weight (Mw) and number average molecular weight (Mn) were determined.
[0072] Equipment: Polymer Char GPC-IR Detector: Polymer Char IR5 Column: Showa Denko UT-807 (1 column) and Tosoh GMHHR-H(S)HT (2 columns) connected in series Mobile phase: Orthodichlorobenzene Column temperature: 140℃ Flow rate: 1.0mL / min Sample concentration: 16mg / 8mL Sample dissolution temperature: 140℃ Sample dissolution time: 60 minutes
[0073] (5) Melting point (DSC) measurement As an index of heat resistance, the melting point of the ethylene-vinyl acetate copolymer resin was measured by the following method. A DSC curve of the ethylene-vinyl acetate copolymer resin was obtained using a PerkinElmer DSC8000 differential scanning calorimeter under the following conditions and procedures.
[0074] 1) Approximately 8.4 mg of a sample of the ethylene-vinyl acetate copolymer resin produced in the Examples and Comparative Examples was placed in an aluminum pan, heated from 0°C to 150°C at 200°C / min, and held at 150°C for 5 minutes. 2) Next, the temperature was lowered from 150°C to 0°C at a rate of 10°C / min, and after the temperature drop was completed, the sample was held at this temperature for 5 minutes. 3) Next, the temperature was increased from 0°C to 150°C at a rate of 10°C / min. From the DSC curve observed in the process 3), the maximum temperature at the melting peak position was taken as the melting point (°C) of the ethylene-vinyl acetate copolymer resin. The higher the melting point, the better the heat resistance.
[0075] (6) Press sheet preparation, thickness measurement, haze measurement A 0.1 mm thick aluminum plate was placed on a 5 mm thick smooth iron plate, and a 50 μm thick polyethylene terephthalate film (Lumirror, manufactured by Toray Industries, Inc.) not coated with cellophane was placed on the aluminum plate. A mold measuring 200 mm in length, 200 mm in width, and 3.1 mm in thickness was placed on top of the aluminum plate, and 130 g of ethylene-vinyl acetate copolymer resin was poured into the mold. The polyethylene terephthalate film was then placed on top of the mold, and the aluminum plate and the iron plate were placed on top of the mold. This was placed in a compression molding machine (SFA-37 manufactured by Shinto Metal Industry Co., Ltd.) whose temperature was adjusted to 180°C, and after preheating at 180°C and 0.1 MPa for 180 seconds, air was removed for 5 seconds (10 MPa), and compression was then performed at 180°C and 15 MPa for 120 seconds. After the pressing was completed, the sample was removed and 5 seconds after removal, it was placed in a compression molding machine (SFA-37 manufactured by Shinto Metal Industry Co., Ltd.) whose temperature was adjusted to 25°C, and cooled while being pressed at 25°C and 10 MPa for 300 seconds to produce a pressed sheet. After cooling, the pressed sheet was removed from the mold and left to stand in an environment at a temperature of 23°C and a humidity of 50% for 24 hours or more. The thickness of the press sheet was measured using a constant pressure thickness gauge (manufactured by TECLOK CORPORATION, model PG-02, minimum display amount 0.001 mm), and a portion of the press sheet with a thickness of 3.1 mm was selected, and the haze value was measured in accordance with ASTM D1003 using a HAZE METER HM-150 manufactured by Murakami Color Research Laboratory Co., Ltd. The smaller the haze value, the more excellent the transparency.
[0076] (7)ESCR To evaluate the environmental stress cracking resistance, the b-ESCR (constant strain environmental stress cracking test) of the ethylene-vinyl acetate copolymer resin was measured in accordance with ASTM D 1693. As the test liquid, 0.5 mass%, 5 mass%, and 10 mass% aqueous solutions of IGEPAL (registered trademark) CO-630 manufactured by Rhodia Nicca Co., Ltd. were used, and the time at which the probability of cracking due to environmental stress reached 50% (hereinafter referred to as F50 value) was measured, and this was taken as the ESCR (environmental stress cracking resistance) value of the ethylene-vinyl acetate copolymer resin. The unit is hr (hours). The larger the value, the better the environmental stress cracking resistance.
[0077] [Example 1] In a tubular reactor, ethylene and 7 mol% vinyl acetate relative to ethylene were introduced, and polymerization was performed at an average polymerization reaction temperature of 218°C and a polymerization pressure of 236 MPa using t-butyl-peroxy-2-ethylhexanoate as a polymerization initiator. After polymerization, the ethylene-vinyl acetate copolymer resin and unreacted materials were introduced into a high-pressure separator at a temperature of 220°C and a pressure of 20 MPa via a double-pipe pipe, and unreacted gas was separated. The inlet temperature of the high-pressure separator was 245°C. Then, the mixture was introduced into a low-pressure separator at a temperature of 180°C and a pressure of 0.04 MPa, and the remaining unreacted gas was separated. 80% by volume of the unreacted gas recovered from the high-pressure separator and the low-pressure separator was sent to the inlet of the multistage compressor and reused for polymerization, 20% by volume of the unreacted gas was separated into ethylene and vinyl acetate in the purification tower-1, and the separated vinyl acetate was returned to the vinyl acetate tank-1 after impurities were removed in the purification tower-2. In addition, the vinyl acetate to be used newly was also returned to the vinyl acetate tank-2 after polymerization inhibitors were removed in the purification tower-2, and the vinyl acetate in the vinyl acetate tank-1 and the vinyl acetate in the vinyl acetate tank-2 (vinyl acetate in tank-1:vinyl acetate in tank-2 (mass ratio)) were mixed in a ratio of 2:1 and sent to the inlet of the multistage compressor for use in polymerization. The obtained molten resin was fed to an extruder and pelletized to obtain an ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 1.
[0078] [Comparative Example 1] The inlet temperature of the high-pressure separator was set to 254°C, 100% by volume of the unreacted gas recovered from the low-pressure separator was sent to the inlet of the multi-stage compressor to be reused for polymerization, and the vinyl acetate to be used again was received directly in the vinyl acetate tank-2 and sent from the vinyl acetate tank-2 to the inlet of the multi-stage compressor to be used for polymerization. The ethylene-vinyl acetate copolymer resin of Comparative Example 1 was obtained by the same operation as in Example 1. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 2.
[0079] [Example 2] In a tubular reactor, ethylene, 7 mol% vinyl acetate relative to ethylene, and 0.17 mol% propylene relative to ethylene were introduced, and polymerization was performed using t-butyl-peroxy-2-ethylhexanoate as a polymerization initiator at an average polymerization reaction temperature of 218°C and a polymerization pressure of 235MPa. After polymerization, the ethylene-vinyl acetate copolymer resin and unreacted materials were introduced into a high-pressure separator at a temperature of 220°C and a pressure of 20MPa through a double-pipe pipe, and the unreacted gas was separated. The inlet temperature of the high-pressure separator was 245°C. Then, the mixture was introduced into a low-pressure separator at a temperature of 180°C and a pressure of 0.04MPa, and the remaining unreacted gas was separated. 60% by volume of the unreacted gas recovered from the high-pressure separator and the low-pressure separator was sent to the inlet of the multistage compressor and reused for polymerization, 40% by volume of the unreacted gas was separated into ethylene and vinyl acetate in the purification tower-1, and the separated vinyl acetate was returned to the vinyl acetate tank-1 after impurities were removed in the purification tower-2. In addition, the vinyl acetate to be used newly was also returned to the vinyl acetate tank-2 after polymerization inhibitors were removed in the purification tower-2, and the vinyl acetate in the vinyl acetate tank-1 and the vinyl acetate in the vinyl acetate tank-2 (vinyl acetate in tank-1:vinyl acetate in tank-2 (mass ratio)) were mixed in a ratio of 2:1 and sent to the inlet of the multistage compressor for use in polymerization. The obtained molten resin was fed to an extruder and pelletized to obtain an ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 1.
[0080] [Comparative Example 2] The inlet temperature of the high-pressure separator was set to 255°C, 60% by volume of the unreacted gas recovered from the low-pressure separator was sent to the inlet of the multi-stage compressor and reused for polymerization, and 40% by volume of the unreacted gas was separated into ethylene and vinyl acetate in the purification tower-1, and the separated vinyl acetate was returned to the vinyl acetate tank-1 after removing impurities in the purification tower-2. In addition, the vinyl acetate to be used newly was received as it was in the vinyl acetate tank-2, and the vinyl acetate in the vinyl acetate tank-1 and the vinyl acetate in the vinyl acetate tank-2 (vinyl acetate in tank-1:vinyl acetate in tank-2 (mass ratio)) were mixed in a ratio of 2:1 and sent to the inlet of the multi-stage compressor for polymerization. An ethylene-vinyl acetate copolymer resin of Comparative Example 2 was obtained by the same operation as in Example 2. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods shown above. The measurement results are shown in Table 2.
[0081] [Example 3] In a tubular reactor, ethylene and vinyl acetate of 7 mol% relative to ethylene were introduced, and polymerization was performed using t-butyl-peroxy-2-ethylhexanoate and di-t-butyl peroxide as polymerization initiators at an average polymerization reaction temperature of 237°C and a polymerization pressure of 264MPa. After polymerization, the ethylene-vinyl acetate copolymer resin and unreacted materials were introduced into a high-pressure separator at a temperature of 220°C and a pressure of 20MPa via a double-pipe pipe, and the unreacted gas was separated. The inlet temperature of the high-pressure separator was 260°C. Then, the mixture was introduced into a low-pressure separator at a temperature of 180°C and a pressure of 0.04MPa, and the remaining unreacted gas was separated. 90% by volume of the unreacted gas recovered from the high-pressure separator and the low-pressure separator was sent to the inlet of the multistage compressor and reused for polymerization, 10% by volume of the unreacted gas was separated into ethylene and vinyl acetate in the purification tower-1, and the separated vinyl acetate was returned to the vinyl acetate tank-1 after impurities were removed in the purification tower-2. In addition, the vinyl acetate to be used newly was also returned to the vinyl acetate tank-2 after polymerization inhibitors were removed in the purification tower-2, and the vinyl acetate in the vinyl acetate tank-1 and the vinyl acetate in the vinyl acetate tank-2 (vinyl acetate in tank-1:vinyl acetate in tank-2 (mass ratio)) were mixed in a ratio of 2:1 and sent to the inlet of the multistage compressor for use in polymerization. The obtained molten resin was fed to an extruder and pelletized to obtain an ethylene-vinyl acetate copolymer resin of Example 3. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 1.
[0082] [Comparative Example 3] An ethylene-vinyl acetate copolymer resin of Comparative Example 3 was obtained by the same operation as in Example 3, except that 100% by volume of the unreacted gas recovered from the low-pressure separator was sent to the inlet of the multistage compressor and reused for polymerization, and the newly used vinyl acetate was received directly in the vinyl acetate tank-2 and sent from the vinyl acetate tank-2 to the inlet of the multistage compressor for use in polymerization. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 2.
[0083] [Example 4] In a tubular reactor, ethylene and 7 mol% vinyl acetate relative to ethylene were introduced, and polymerization was performed using t-butyl-peroxy-2-ethylhexanoate and di-t-butyl peroxide as polymerization initiators at an average polymerization reaction temperature of 224°C and a polymerization pressure of 264MPa. After polymerization, the ethylene-vinyl acetate copolymer resin and unreacted materials were introduced into a high-pressure separator at a temperature of 230°C and a pressure of 20MPa via a double-pipe pipe, and the unreacted gas was separated. The inlet temperature of the high-pressure separator was 244°C. Then, the mixture was introduced into a low-pressure separator at a temperature of 190°C and a pressure of 0.04MPa, and the remaining unreacted gas was separated. 70% by volume of the unreacted gas recovered from the high-pressure separator and the low-pressure separator was sent to the inlet of the multistage compressor and reused for polymerization, 30% by volume of the unreacted gas was separated into ethylene and vinyl acetate in the purification tower-1, and the separated vinyl acetate was returned to the vinyl acetate tank-1 after impurities were removed in the purification tower-2. In addition, the vinyl acetate to be used newly was also returned to the vinyl acetate tank-2 after polymerization inhibitors were removed in the purification tower-2, and the vinyl acetate in the vinyl acetate tank-1 and the vinyl acetate in the vinyl acetate tank-2 (vinyl acetate in tank-1:vinyl acetate in tank-2 (mass ratio)) were mixed in a ratio of 2:1 and sent to the inlet of the multistage compressor for use in polymerization. The obtained molten resin was fed to an extruder and pelletized to obtain an ethylene-vinyl acetate copolymer resin of Example 4. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 1.
[0084] [Comparative Example 4] The inlet temperature of the high-pressure separator was set to 254°C, 100% by volume of the unreacted gas recovered from the low-pressure separator was sent to the inlet of the multi-stage compressor to be reused for polymerization, and the vinyl acetate to be used freshly was received directly in the vinyl acetate tank-2, sent from the vinyl acetate tank-2 to the inlet of the multi-stage compressor to be used for polymerization. An ethylene-vinyl acetate copolymer resin of Comparative Example 4 was obtained by the same operation as in Example 4. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 2.
[0085] [Example 5] In a tubular reactor, ethylene and 7.5 mol% vinyl acetate relative to ethylene were introduced, and polymerization was performed using t-butyl-peroxy-2-ethylhexanoate as a polymerization initiator at an average polymerization reaction temperature of 215°C and a polymerization pressure of 264MPa. After polymerization, the ethylene-vinyl acetate copolymer resin and unreacted materials were introduced into a high-pressure separator at a temperature of 200°C and a pressure of 22MPa through a double-pipe pipe, and the unreacted gas was separated. The inlet temperature of the high-pressure separator was 238°C. Then, the mixture was introduced into a low-pressure separator at a temperature of 170°C and a pressure of 0.04MPa, and the remaining unreacted gas was separated. 70% by volume of the unreacted gas recovered from the high-pressure separator and the low-pressure separator was sent to the inlet of the multistage compressor and reused for polymerization, 30% by volume of the unreacted gas was separated into ethylene and vinyl acetate in the purification tower-1, and the separated vinyl acetate was returned to the vinyl acetate tank-1 after impurities were removed in the purification tower-2. In addition, the vinyl acetate to be used newly was also returned to the vinyl acetate tank-2 after polymerization inhibitors were removed in the purification tower-2, and the vinyl acetate in the vinyl acetate tank-1 and the vinyl acetate in the vinyl acetate tank-2 (vinyl acetate in tank-1:vinyl acetate in tank-2 (mass ratio)) were mixed in a ratio of 2:1 and sent to the inlet of the multistage compressor for use in polymerization. The obtained molten resin was fed to an extruder and pelletized to obtain an ethylene-vinyl acetate copolymer resin of Example 5. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 1.
[0086] [Comparative Example 5] The inlet temperature of the high-pressure separator was set to 252°C, 100% by volume of the unreacted gas recovered from the low-pressure separator was sent to the inlet of the multistage compressor to be reused for polymerization, and the vinyl acetate to be used again was received directly in the vinyl acetate tank-2 and sent from the vinyl acetate tank-2 to the inlet of the multistage compressor to be used for polymerization. An ethylene-vinyl acetate copolymer resin of Comparative Example 5 was obtained by the same operation as in Example 5. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 2.
[0087] [Example 6] In a tubular reactor, ethylene and 8 mol% vinyl acetate relative to ethylene were introduced, and polymerization was performed at an average polymerization reaction temperature of 215°C and a polymerization pressure of 264 MPa using t-butyl-peroxy-2-ethylhexanoate as a polymerization initiator. After polymerization, the ethylene-vinyl acetate copolymer resin and unreacted materials were introduced into a high-pressure separator at a temperature of 220°C and a pressure of 20 MPa via a double-pipe pipe, and unreacted gas was separated. The inlet temperature of the high-pressure separator was 235°C. Then, the mixture was introduced into a low-pressure separator at a temperature of 180°C and a pressure of 0.04 MPa, and the remaining unreacted gas was separated. 70% by volume of the unreacted gas recovered from the high-pressure separator and the low-pressure separator was sent to the inlet of the multistage compressor and reused for polymerization, 30% by volume of the unreacted gas was separated into ethylene and vinyl acetate in the purification tower-1, and the separated vinyl acetate was returned to the vinyl acetate tank-1 after impurities were removed in the purification tower-2. In addition, the vinyl acetate to be used newly was also returned to the vinyl acetate tank-2 after polymerization inhibitors were removed in the purification tower-2, and the vinyl acetate in the vinyl acetate tank-1 and the vinyl acetate in the vinyl acetate tank-2 (vinyl acetate in tank-1:vinyl acetate in tank-2 (mass ratio)) were mixed in a ratio of 2:1 and sent to the inlet of the multistage compressor for use in polymerization. The obtained molten resin was fed to an extruder and pelletized to obtain an ethylene-vinyl acetate copolymer resin of Example 6. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 1.
[0088] [Example 7] In a tubular reactor, ethylene, 6.5 mol% vinyl acetate relative to ethylene, and 0.17 mol% propylene relative to ethylene were introduced, and polymerization was performed using t-butyl-peroxy-2-ethylhexanoate as a polymerization initiator at an average polymerization reaction temperature of 218°C and a polymerization pressure of 235MPa. After polymerization, the ethylene-vinyl acetate copolymer resin and unreacted materials were introduced into a high-pressure separator at a temperature of 220°C and a pressure of 20MPa through a double-pipe pipe, and the unreacted gas was separated. The inlet temperature of the high-pressure separator was 233°C. Then, the mixture was introduced into a low-pressure separator at a temperature of 180°C and a pressure of 0.04MPa, and the remaining unreacted gas was separated. 60% by volume of the unreacted gas recovered from the high-pressure separator and the low-pressure separator was sent to the inlet of the multistage compressor and reused for polymerization, 40% by volume of the unreacted gas was separated into ethylene and vinyl acetate in the purification tower-1, and the separated vinyl acetate was returned to the vinyl acetate tank-1 after impurities were removed in the purification tower-2. In addition, the vinyl acetate to be used newly was also returned to the vinyl acetate tank-2 after polymerization inhibitors were removed in the purification tower-2, and the vinyl acetate in the vinyl acetate tank-1 and the vinyl acetate in the vinyl acetate tank-2 (vinyl acetate in tank-1:vinyl acetate in tank-2 (mass ratio)) were mixed in a ratio of 2:1 and sent to the inlet of the multistage compressor for use in polymerization. The obtained molten resin was fed to an extruder and pelletized to obtain an ethylene-vinyl acetate copolymer resin of Example 7. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 1.
[0089] [Example 8] The vinyl acetate to be used freshly was received as it was in the vinyl acetate tank-2, and the vinyl acetate in the vinyl acetate tank-1 and the vinyl acetate in the vinyl acetate tank-2 were mixed in a ratio of 2:1 (vinyl acetate in tank-1:vinyl acetate in tank-2 (mass ratio)) and sent to the inlet of the multi-stage compressor for polymerization. The ethylene-vinyl acetate copolymer resin of Example 8 was obtained by the same operation as in Example 2. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 1.
[0090] [Example 9] An ethylene-vinyl acetate copolymer resin of Example 9 was obtained by the same procedure as in Example 3, except that the inlet temperature of the high-pressure separator was set to 233°C. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 1.
[0091] [Comparative Example 6] The inlet temperature of the high-pressure separator was set to 252°C, 100% by volume of the unreacted gas recovered from the low-pressure separator was sent to the inlet of the multi-stage compressor to be reused for polymerization, and the vinyl acetate to be used again was received directly in the vinyl acetate tank-2 and sent from the vinyl acetate tank-2 to the inlet of the multi-stage compressor to be used for polymerization. An ethylene-vinyl acetate copolymer resin of Comparative Example 6 was obtained by the same operation as in Example 6. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 2.
[0092] [Comparative Example 7] The inlet temperature of the high-pressure separator was set to 254°C, 100% by volume of the unreacted gas recovered from the low-pressure separator was sent to the inlet of the multi-stage compressor to be reused for polymerization, and the vinyl acetate to be used again was received directly in the vinyl acetate tank-2 and sent from the vinyl acetate tank-2 to the inlet of the multi-stage compressor to be used for polymerization. An ethylene-vinyl acetate copolymer resin of Comparative Example 7 was obtained by the same operation as in Example 3. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 2.
[0093] [Comparative Example 8] The inlet temperature of the high-pressure separator was set to 277°C, 100% by volume of the unreacted gas recovered from the low-pressure separator was sent to the inlet of the multi-stage compressor to be reused for polymerization, and the vinyl acetate to be used freshly was received directly in the vinyl acetate tank-2 and sent from the vinyl acetate tank-2 to the inlet of the multi-stage compressor to be used for polymerization. The ethylene-vinyl acetate copolymer resin of Comparative Example 8 was obtained by the same operation as in Example 3. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 2.
[0094] [Comparative Example 9] The inlet temperature of the high-pressure separator was set to 254°C, 100% by volume of the unreacted gas recovered from the low-pressure separator was sent to the inlet of the multi-stage compressor and reused for polymerization, and the vinyl acetate to be used again was removed of polymerization inhibitors and sent from the vinyl acetate tank-2 to the inlet of the multi-stage compressor and used for polymerization. The same operations as in Example 1 were performed to obtain an ethylene-vinyl acetate copolymer resin of Comparative Example 9. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 2.
[0095] [Comparative Example 10] The inlet temperature of the high-pressure separator was set to 260°C, 100% by volume of the unreacted gas recovered from the low-pressure separator was sent to the inlet of the multi-stage compressor to be reused for polymerization, and the vinyl acetate to be used again was removed of polymerization inhibitors and sent from the vinyl acetate tank-2 to the inlet of the multi-stage compressor to be used for polymerization. The ethylene-vinyl acetate copolymer resin of Comparative Example 10 was obtained by the same operation as in Example 3. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods described above. The measurement results are shown in Table 2.
[0096] [Table 1]
[0097] [Table 2]
Claims
1. The content of vinyl acetate units is 10.0% by mass or more and 20.0% by mass or less, The storage modulus G′ during the temperature drop process under the temperature drop measurement conditions of the melt viscoelasticity measurement described below satisfies the following formula (1) within a range satisfying the following formula (2), An ethylene-vinyl acetate copolymer resin having an MFR of 0.1 g / 10 min or more and 5.0 g / 10 min or less. Tb-Te≦10.00 (1) (In formula (1), Tb is the maximum temperature (° C.) within the range satisfying the following formula (2), and Te is the minimum temperature (° C.) within the range satisfying the following formula (2).) |(dlogG' / dT)|≧0.04 (2) (In formula (2), |(dlog G' / dT)| is the degree of change in storage modulus G' (Pa) with respect to the change in temperature T (°C).) (Melt viscoelasticity measurement conditions) Measuring device: ARES-G2 (manufactured by TA Instruments) Atmosphere: Nitrogen Geometry: 8mmφ parallel plate Gap distance: 1.5 mm Distortion: 5.0% at 105° C. or more and 200° C. or less, 3.0% at 45° C. or more and less than 105° C., 0.1% at 30° C. or more and less than 45° C. The temperature indicated is the temperature directly below the disk of the parallel plate. Temperature drop measurement conditions: A sample is placed in an apparatus set at 200° C. and held for 10 minutes. The temperature of the sample is then lowered from 200° C. to 30° C. at a rate of 5° C. / min, and the melt viscoelasticity of the sample during the temperature drop is measured.
2. The storage modulus G' during the temperature drop process under the temperature drop measurement conditions of the melt viscoelasticity measurement is expressed by the following formula: The ethylene vinyl acetate copolymer resin according to claim 1, which satisfies (3). |(dloG' / dT)| MAX ≧-0.0125×VA content+0.490 (3) (In formula (3), |(dlogG' / dT)| MAX is the maximum value of the degree of change in storage modulus G' (Pa) with respect to the change in temperature T (°C), and the VA content is the content (mass%) of vinyl acetate units in the ethylene-vinyl acetate copolymer resin.
3. The ethylene-vinyl acetate copolymer resin according to claim 1 or 2, wherein the ethylene-vinyl acetate copolymer resin has a molecular weight distribution (Mw / Mn) of 2.0 or more and 8.0 or less.
4. A molded article comprising the ethylene-vinyl acetate copolymer according to any one of claims 1 to 3.
5. A film comprising the ethylene-vinyl acetate copolymer according to any one of claims 1 to 3.
6. A laminated film comprising the ethylene-vinyl acetate copolymer according to any one of claims 1 to 3.
Citation Information
Patent Citations
Production of ethylene-vinyl acetate copolymer excellent in heat resistance and mechanical characteristic
JP1998130307A
Ethylene-vinyl acetate copolymer film
JP2004161881A
Ethylene / vinyl acetate copolymer and hot-melt adhesive composition comprising the same
JP2005272744A
Ethylene-vinyl acetate copolymer resin, sheet molding prepared therewith, solar cell sealing material, solar cell module, and method for producing ethylene-vinyl acetate copolymer resin
JP2017078136A
Manufacturing method of ethylene vinyl acetate copolymer resin for solar cell encapsulation material sheet and resin manufactured by the manufacturing method
JP2017115118A